Malaysia : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2020 Article IV Consultation highlights that the Malaysian economy is stable despite domestic and external challenges. The authorities are making progress on their reform agenda including governance reforms and measures to improve the transparency and management of public finances. Policies should focus on medium-term fiscal consolidation, while safeguarding growth and financial stability. Structural reforms are needed to enshrine in law main governance measures, and to boost productivity to achieve high income status and inclusive growth. Growth has held up and inflation has remained subdued. Domestic demand is expected to be the main driver of growth over the medium term. Risks to the outlook are, on balance, to the downside. It is recommended to that medium-term fiscal consolidation plans should be underpinned by well-identified revenue and spending measures. Pushing ahead with structural fiscal reforms, including the adoption of a Fiscal Responsibility Act, as well as improvement in debt management, public procurement, and the public investment framework is important.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet